Promoción y prevención en salud oral dirigida a la población adolescente del instituto ACOANDES (2023)
The promotion and prevention of oral health in the adolescents of the ACOANDES institute was adequately encouraged, since the students participated voluntarily and enthusiastically in the different educational activities. The education provided had a positive impact, since the results showed that their level of knowledge increased after the educational intervention.